Mouthguard BITES (Behavior, Impulsivity, Theory Evaluation Study): What Drives Mouthguard Use Among High School Basketball and Baseball/Softball Athletes - Collins, Christy L. (J Prim Prev, 2015)
Although mouthguards are effective, inexpensive, easy to use, and readily available, this form of protective equipment has been underutilized. “Impulsive delay discounting” (an index of impulsive behavior) among high school athletes may help explain their decision making regarding use of protective equipment such as mouthguards. We investigated the relationship between high school baseball, softball, and basketball players’ mouthguard use, impulsive delay discounting, and the precaution adoption process model (a behavior change theory). A convenience sample of boys’ and girls’ basketball and baseball/softball players at 21 high schools in the Greater Columbus, Ohio, metro area completed a self-administered survey that captured their demographic information, knowledge, attitudes, and beliefs regarding mouthguard use, impulsive delay discounting, and precaution adoption process model stage. We surveyed a total of 1636 students (55.9 % male, 43.8 % female, 0.3 % unknown). Only 12.3 % reported using a mouthguard either every time or sometimes during practice or competition. The primary reasons reported for not wearing mouthguards were they were not required to (65.3 %) and that the athletes could not breathe or talk while wearing one (61.5 %). These reasons were consistent across sex and sport. Most athletes reported that their coaches (87.3 %) and parents (64.5 %) had never talked to them about wearing a mouthguard. Lower precaution adoption process model stage was significantly associated with higher impulsivity (p < 0.001) and higher delayed discounting (p = 0.016) after adjusting for school, sport, and sex. Voluntary mouthguard use among high school athletes playing basketball and baseball/softball remains low despite the risk of dental injury in these sports. Effective, evidence-based, targeted, and tailored interventions to improve adolescent athletes’ use of mouthguards to prevent sports-related dental injuries should be based on the specific behavioral and social factors influencing each athlete’s decision making regarding use of mouthguards.